Pengaruh Profitabilitas, Likuiditas, Leverage, dan Efisiensi Operasional terhadap Financial Distress pada Perusahaan Sub Sektor Food and Staples Retailing yang Terdaftar di ISSI Periode 2020-2024 - Fitri Yumi Aulia; Khadijah Nurani (Lembaga Yasin AlSys, 2026)
Although financial distress has received considerable attention in various studies because it constitutes an initial condition that may lead to corporate bankruptcy, research on the effects of profitability, liquidity, leverage, and operating efficiency on financial distress among food and staples retailing subsector companies listed on the Indonesian Sharia Stock Index (ISSI) remains limited. This study aimed to analyze the effects of profitability, liquidity, leverage, and operating efficiency on financial distress among food and staples retailing subsector companies listed on the ISSI during the 2020–2024 period. This study employed a quantitative approach with a causal research design. The research sample consisted of nine companies selected through purposive sampling, resulting in 45 observations. Secondary data in the form of annual financial statements were collected through a documentation study and analyzed using panel data regression with the assistance of EViews 13. The results showed that profitability, liquidity, and leverage had significant effects on financial distress, whereas operating efficiency had no significant effect. Simultaneously, profitability, liquidity, leverage, and operating efficiency had a significant effect on financial distress, with an adjusted R² value of 98.3162%. These findings support the relevance of signaling theory and trade-off theory in explaining the relationship between financial ratios and financial distress conditions. This study provides an empirical contribution to the development of financial management research and may serve as a consideration for corporate management and investors in detecting and minimizing the risk of financial distress.